Thalamo-cortical coupling during encoding and consolidation is linked to durable memory formation - Wagner, Isabella C.; van Buuren, Mariët; Fernández, Guillén (NeuroImage (Orlando, Fla.), 2019)
Memory formation transforms experiences into durable engrams. The stabilization critically depends on processes during and after learning, and involves hippocampal-medial prefrontal interactions that appear to be mediated by the nucleus reuniens of the thalamus in rodents, which corresponds to the human medioventral thalamus. How this region contributes to durable memory formation in humans is, however, unclear. Furthermore, the anterior-, lateral dorsal-, and mediodorsal nuclei appear to promote mnemonic function as well. We hypothesized that durable memory formation is associated with increases in thalamo-cortical interactions during encoding and consolidation. Thirty-three human subjects underwent fMRI while studying picture-location associations. To assess consolidation, resting-state brain activity was measured after study and was compared to a pre-study baseline. Memory was tested on the same day and 48 h later. While “weak” memories could only be remembered at the immediate test, “durable” memories persisted also after the delay. We found increased coupling of the medioventral-, adjacent anterior-, lateral dorsal-, and mediodorsal thalamus with the hippocampus and surrounding medial temporal lobe, as well as with anterior and posterior midline regions related to durable memory encoding. The medioventral and lateral dorsal thalamus showed increased connectivity with posterior medial and parietal cortex from baseline to post-encoding rest, positively scaling with the proportion of durable memories formed across subjects. Additionally, the lateral dorsal thalamus revealed consolidation-related coupling with the inferior temporal, retrosplenial, and medial prefrontal cortex. We suggest that thalamo-cortical cross-talk strengthens mnemonic representations at initial encoding, and that cortical coupling of specific thalamic subregions supports consolidation thereafter. •Thalamo-cortical interactions support memory encoding.•Medioventral and lateral dorsal thalamic connectivity supports consolidation.•Thalamo-cortical effects are specifically linked to durable memory formation.